The relationship between smartphone use and adolescent sleep quality at Mojoagung state Senior High School - Ayu Rahmadiani Nur Oktavia; Supriliyah Praningsih (Journal of Clinical Nursing Studies and Practice, 2026)
A factor substantially influencing the stability of Muslim faith is the rapid development of digital technology, which has led to an increase in smartphone use among young people. Analyzing the relationship between smartphone use and sleep quality is the primary objective of this study. This study was conducted at Mojoagung State Senior High School, which has high academic standards. Methods: This study used a cross- sectional design for its analysis. The study population was 315 adults from Mojoagung State Senior High School, with 76 respondents randomly selected using a sampling technique. The SASSV questionnaire was used to collect smartphone usage data. Sleep quality was assessed using the PSQI. The results and analysis showed that the majority of respondents (57.9%) were high-income smartphone users, and the majority (71.1%) reported poor sleep quality. With a correlation coefficient of 0.360, the Spearman's Rho test yielded a significance value of p=0.001. This indicates a relationship between smartphone use and sleep quality. Women's sleep quality is negatively affected by their increasing dependence on smartphones. Discussion: This study recommends specific smartphone usage strategies, including white noise masking and at least 60 minutes of social media use before bedtime, to prevent eyestrain. Furthermore, collaboration between schools and parents is essential to facilitate high-quality programs for students to address attention deficits and optimize academic performance.